2022
DOI: 10.3390/ijms23031863
|View full text |Cite
|
Sign up to set email alerts
|

Cytoprotective Activity of Polyamines Is Associated with the Alternative Splicing of RAD51A Pre-mRNA in Normal Human CD4+ T Lymphocytes

Abstract: Physiological polyamines are ubiquitous polycations with pleiotropic biochemical activities, including regulation of gene expression and cell proliferation as well as modulation of cell signaling. They can also decrease DNA damage and promote cell survival. In the present study, we demonstrated that polyamines have cytoprotective effects on normal human CD4+ T lymphocytes but not on cancer Jurkat or K562 cells. Pretreatment of lymphocytes with polyamines resulted in a significant reduction in cells with DNA da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 72 publications
(72 reference statements)
1
4
0
Order By: Relevance
“…Previously, it was shown that exogenous PAs can promote tumor and normal cell proliferation [43] and provide a cytoprotective action for normal fibroblasts [44]. In accordance, we demonstrated the promotion of WI-38 and HepG2 viability after cell incubation with PAs (Figure 4A,B).…”
Section: Discussionsupporting
confidence: 89%
“…Previously, it was shown that exogenous PAs can promote tumor and normal cell proliferation [43] and provide a cytoprotective action for normal fibroblasts [44]. In accordance, we demonstrated the promotion of WI-38 and HepG2 viability after cell incubation with PAs (Figure 4A,B).…”
Section: Discussionsupporting
confidence: 89%
“…Base-pairing to target pre-mRNA blocks the binding of SR proteins to their binding sites, leading to the retention of associated exons and the inclusion of them into mature mRNA. The modulation of cellular functions by SSOs has been shown by us in several previous studies [34,80,81]. Using SSOs targeting sensitive cis-elements on exon 2 and exon 7, we produced Tregs with selective expression of FL FoxP3 (Figure 2).…”
Section: Discussionmentioning
confidence: 79%
“…To modulate exon 2 and exon 7 alternative splicing in Tregs and to create a Treg cell line expressing only one of four possible FoxP3 splice variants, we created 36-mer splice-switching oligonucleotides (SSOs). They could base-pair to splicing regulatory sequences and induce deletion ( Figure 3 A,B) or retention of exon 2 or of exon 7 ( Figure 4 A,B) [ 31 , 32 , 33 ]. Tregs from four HDs (donors 9, 10, 11, and 12) were transfected with each single oligonucleotide, and the expression of FoxP3 splice variants was examined four days after transfection.…”
Section: Resultsmentioning
confidence: 99%
“…Modulation of pre-mRNA AS by SSO targeting splicing regulatory cis -elements has been shown by us in several studies on other objects [ 21 , 33 , 71 ], and we used this approach to induce a single FoxP3 splice variant in Tregs. As expected, the use of a single SSO inducing only one exon (2 or 7, Figure 3 and Figure 4 ) insertion or deletion did not allow us to obtain cells with only one splice variant.…”
Section: Discussionmentioning
confidence: 99%